PELAYANAN KEAGAMAAN MASYARAKAT PERBATASAN (Studi Kasus di Kabupaten Belu Nusa Tenggara Timur) - Muhtar Muhtar (Harmoni, 2015)
The research aims to discover the religious services, problems, and social cultural interaction between border area communities and Timor Leste communities. The result shows that the religious living in Belu border area and Malaka indicates tolerant, conducive, and harmonious condition. Some areas that show religious tolerance are Kletek and Suai. Their communities consisting of Islam, Chatolicism, and Protestantism are amicable because they have strong kinship. Overall, the communties have not got the sufficient services undertaken by Ministry of religious affairs in Belu regency. The limited budget to hold some program also occurs. Additionally, It is required to add some committee for Hinduism, Buddhism, and Confucianism in organization structure in Ministry of religious affairs in Belu regency.